The Relevance of Maqāṣid al-Sharī‘ah in Modern Governance - Rifqah Husnul Khatimah; Duski Samad; Firdaus Mamad (The Future of Education Journal, 2025)
The development of modern governance presents complex ethical, institutional, and social challenges, particularly in the context of globalization, digitalization, and increasing organizational complexity. Amid growing demands for transparent, accountable, and people-centered governance, maqāṣid al-sharīʿah offers a comprehensive ethical and normative framework capable of addressing these challenges. This article highlighting the urgency of understanding the concept of Islamic law and maqashid sharia in the context of Islamic religious education. In this context, an in-depth understanding of the principles of Islamic law and maqashid sharia is considered very important to strengthen the foundation of Islamic teachings in the education system.This study aims to examine the relevance and contribution of maqāṣid al-sharīʿah to strengthening modern governance practices across public administration, corporate governance, and contemporary social institutions. Employing a qualitative descriptive approach through a systematic literature review. The findings indicate that the core principles of maqāṣid al-sharīʿah including the protection of religion, life, intellect, property, progeny and environment are strongly aligned with fundamental principles of modern governance, such as justice, accountability, transparency, inclusiveness, and sustainability. Moreover, maqāṣid al-sharīʿah can function not only as an ethical foundation but also as an operational and evaluative framework for public policymaking, economic governance, anti-corruption initiatives, and institutional management in the digital era. This study concludes that integrating maqāṣid al-sharīʿah into modern governance has the potential to enhance moral legitimacy, policy effectiveness, and holistic human well-being, thereby contributing to sustainable and value-based governance systems.